2007
DOI: 10.1158/0008-5472.can-07-1687
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Screen Identifies Anisomycin as an Anoikis Sensitizer That Functions by Decreasing FLIP Protein Synthesis

Abstract: Malignant epithelial cells with metastatic potential resist apoptosis that normally occurs upon loss of anchorage from the extracellular matrix, a process termed ''anoikis.'' Resistance to anoikis enables malignant cells to survive in an anchorage-independent manner, which leads to the formation of distant metastases. To understand the regulation of anoikis, we designed, automated, and conducted a high-throughput chemical screen for anoikis sensitizers. PPC-1 anoikisresistant prostate cancer cells were seeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 42 publications
2
78
1
1
Order By: Relevance
“…Our results showed SB203580 significantly inhibits activation of Hsp27 which is the downstream substrate of p38MAPK but does not inhibit the phosphorylation of p38MAPK, indicating that SB203580 inhibit p38MAPK activity but not its activation. For SP600125, we demonstrated it significantly inhibits the phosphorylation of JNK (Figure 2 Anisomycin induces U251 and U87 cell death independent of its ability to sensitize cells to anoikis Caspase-8 and the caspase-8 inhibitor FLIP have been reported to participate in anisomycin-induced apoptosis [6] . Anisomycin can induce apoptosis by decreasing levels of FLIP, resulting in a sensitization of cells to anoikis.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Our results showed SB203580 significantly inhibits activation of Hsp27 which is the downstream substrate of p38MAPK but does not inhibit the phosphorylation of p38MAPK, indicating that SB203580 inhibit p38MAPK activity but not its activation. For SP600125, we demonstrated it significantly inhibits the phosphorylation of JNK (Figure 2 Anisomycin induces U251 and U87 cell death independent of its ability to sensitize cells to anoikis Caspase-8 and the caspase-8 inhibitor FLIP have been reported to participate in anisomycin-induced apoptosis [6] . Anisomycin can induce apoptosis by decreasing levels of FLIP, resulting in a sensitization of cells to anoikis.…”
Section: Resultsmentioning
confidence: 93%
“…More recently, it was found that not only endothelial cells and nonmalignant epithelial cells but also malignant epithelial cells could undergo anoikis through self-initiated activation of the death receptor signaling pathway [17][18][19][20] . The results from these studies suggested that anisomycin initiates anoikis in a caspase-8-dependent manner, due to its inhibition of FLIP protein synthesis, and independent of its ability to activate JNK and p38 [6] . To investigate whether anisomycin initiates anoikis in U251 and U87 cells, we detected the expression of fulllength caspase-8, cleaved caspase-8 and FLIP protein by Western blotting.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, they showed that SAHA disrupts the FLIP/ Ku70 complex via increasing the acetylation of Ku70, which consequently triggers FLIP polyubiquitination and degradation by the proteasome (Kerr et al, 2012). C-FLIP has been demonstrated to be down-regulated by several compounds such as actinomycin D (Hernandez et al, 2001), cycloheximide (Kaminskyy et al, 2013), and anisomycin (Mawji et al, 2007a); the first is an RNA synthesis inhibitor, and the second and third are protein synthesis inhibitors. Moreover, protease inhibitors such as Bortezomib (PS-34) have been extensively studied and shown to have the ability to reduce c-FLIP in diverse cell lines (Koschny et al, 2007;Perez et al, 2010).…”
Section: Targeting C-flipmentioning
confidence: 99%